2008
DOI: 10.1088/0953-4075/41/19/195503
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement of a general formalism Λ-type three-level atom interacting with a non-correlated two-mode cavity field in the presence of nonlinearities

Abstract: We investigate the evolution of the atomic quantum entropy and the atom–field entanglement in a system of a Λ-configuration three-level atom interacting with a two-mode field with additional forms of nonlinearities of both the field and the intensity-dependent atom–field coupling. With the derivation of the unitary operator within the frame of the dressed state and the exact results for the state of the system we perform a careful investigation of the temporal evolution of the entropy. A factorization of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…The state of the qutrit can be spanned by the three orthogonal basis |0 , |1 , |2 . Physically, qutrit can be represented by three-level atoms [23,24,25] (see Fig.(1d)). In this treatment, we consider only one qutrit is driven by the CERF, where both qutrits are initially prepared in Λ configuration.…”
Section: Dynamics Of Qutrit-qutrit Systemmentioning
confidence: 99%
“…The state of the qutrit can be spanned by the three orthogonal basis |0 , |1 , |2 . Physically, qutrit can be represented by three-level atoms [23,24,25] (see Fig.(1d)). In this treatment, we consider only one qutrit is driven by the CERF, where both qutrits are initially prepared in Λ configuration.…”
Section: Dynamics Of Qutrit-qutrit Systemmentioning
confidence: 99%
“…For example, atom-photon entanglement in the interaction between a V-type three-level atom and single-mode cavity field in a Kerr medium with intensity-dependent coupling has been studied by Obada et al [19]. In addition, atom-photon entanglement in a Λ-type [20,21] and cascade [22] three-level atom interacting with a non-correlated two-mode cavity field has been investigated in the presence of Kerr nonlinearity. Furthermore, in the context of semi-classical theory of atom-light interaction, it has been shown that the induced steady state entanglement between an atom and its spontaneous emission can be controlled by intensity and detuning parameter of an applied field [23].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, similar to references [20,21], we consider a  -type three-level atom that interacts with a non-correlated two-mode quantized field in a lossless cavity in the presence both Kerr and cross-Kerr nonlinearity. The atom-field coupling is assumed to possess some admissible intensity dependence.…”
Section: Introductionmentioning
confidence: 99%
“…[9]. Also, the evolution of the atomic or field entropy when a three-level atom interacts with one-mode [10,11] and two-mode [12][13][14][15] cavity fields has also been examined. More recently, Obada and Eied studied the entropy of a system composed of a Ξ -type three-level atom interacting with a non-correlated two-mode cavity field in the presence of nonlinearities [16].…”
Section: Introductionmentioning
confidence: 99%